A Review of Slope Stability Analysis Using Artificial Neural Networks: Review: Analisis Kestabilan Lereng Menggunakan Artificial Neural Network - Risaldi Hidayat (ReTII, 2022)
Over the last few years, arificial neural network (ANN) have been used successfully for modeling almost all aspect of geotechnical engineering problems especially in slope stability. Based on the comparison in this paper, that ANN has many advantages if the problem cannot be solved by mathematically and handle large data set. There are various intelligent algorithms available, therefore ANN is not a new concept. However, ANN’s ability to solve complex geotechnical engineering problems (such as, which is found within the slope stability analysis) is its main advantage. So, this paper to provide an overview of ANN modeling in slope stability analysis as part of geotechnical engineering problems and research direction of ANN that needs further attention in the future.